IMPLEMENTASI E-LEARNING DALAM PROSES PEMBELAJARAN BAGI MAHASISWA BARU DI FAKULTAS TEKNOLOGI INFORMASI - Sinta, Sinta; Marini, Marini; andika, Andika; Riance, Astri (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Riau, 2025)
The implementation of e-learning in higher education institutions has transformed the learning paradigm from traditional classroom settings to digital and interactive environments. This research focuses on the implementation of an e-learning system at the Faculty of Information Technology to support new students in adapting to digital-based academic processes. The system was designed using Moodle integrated with institutional authentication, Google Workspace for Education, and cloud storage. A pre-test and post-test experimental method was used to measure its effectiveness on learning outcomes, participation rates, and digital literacy levels among new students. The findings revealed that students’ average learning performance increased by 18%, participation by 45%, and digital competency by 27% after using the platform. These results indicate that the integration of e-learning significantly improves learning flexibility, engagement, and technological proficiency for first-year students.